A one-pot synthesis of trichloromethylated pyrimidines from trichloroacetimidamides and acetylenic esters. Issue 16 (20th April 2016) - Yavari, Issa; Malekafzali, Alaleh; Eivazzadeh-Keihan, Reza; Skoulika, Stavroula; Alivaisi, Rahman
Graphical abstract: Abstract: A one-pot synthesis of functionalized trichloromethylated pyrimidines from the reaction of trichloroacetimidamides, generated by the addition of guanidine derivatives to trichloroacetonitrile, and acetylenic esters, in good yields is described.